Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1360-0443.2009.02777.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of repetitive transcranial magnetic stimulation in alcohol dependence: a sham‐controlled study

Abstract: Right dorsolateral pre-frontal high-frequency rTMS was found to have significant anticraving effects in alcohol dependence. The results highlight the potential of rTMS which, combined with other anticraving drugs, can act as an effective strategy in reducing craving and subsequent relapse in alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
145
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(159 citation statements)
references
References 23 publications
(33 reference statements)
9
145
1
4
Order By: Relevance
“…The level of alcohol craving was assessed with the Alcohol Craving Questionnaire (ACQ-NOW) before and after rTMS treatment, and 1 month following. The results of the study demonstrated a signifi cant reduction in the level of craving scores in patients who received active compared to sham rTMS (Mishra et al, 2010). Although this study was single blind and by extension susceptible to rater bias, it provides support for the ability of high frequency rTMS over the right DLPFC to reduce alcohol cravings.…”
Section: Treatment Of Alcoholism With Rtmsmentioning
confidence: 74%
See 2 more Smart Citations
“…The level of alcohol craving was assessed with the Alcohol Craving Questionnaire (ACQ-NOW) before and after rTMS treatment, and 1 month following. The results of the study demonstrated a signifi cant reduction in the level of craving scores in patients who received active compared to sham rTMS (Mishra et al, 2010). Although this study was single blind and by extension susceptible to rater bias, it provides support for the ability of high frequency rTMS over the right DLPFC to reduce alcohol cravings.…”
Section: Treatment Of Alcoholism With Rtmsmentioning
confidence: 74%
“…In spite of the availability of several anti-craving medications (e.g. acamprosate and naltrexone) the effi cacy of these drugs is limited for alcohol dependence (Mishra et al, 2010). Similar to the lines of evidences for the potential of rTMS to treat nicotine dependence, such as its action on the neurotransmitter systems including dopamine and GABA, rTMS has also been examined for its ability to treat alcohol dependence.…”
Section: Pathophysiology Of Alcohol Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, whether the increase of PAS-induced LTD-like plasticity in motor cortex by low-dose ethanol provides a surrogate marker for the addictive potential of ethanol in given individuals would require further deliberate testing. On the other hand, it is of interest to note that several recent therapeutic trials applied high-frequency repetitive TMS to the dorsolateral prefrontal cortex of alcohol addicts and observed a decrease in spontaneous alcohol craving (Gorelick et al, 2014;Höppner et al, 2011;Mishra et al, 2010). High-frequency repetitive TMS typically leads to LTPlike plasticity (for review, ) so that these therapeutic effects may be explained by counteracting LTDdependent mechanisms of addiction, in addition to other potential mechanisms, such as modulation of dopaminergic neurotransmission in addiction-related subcortical target areas of the dorsolateral prefrontal cortex (Feil and Zangen, 2010;Naim-Feil and Zangen, 2013).…”
Section: Behavioral Significance Of the Present Findingsmentioning
confidence: 99%
“…Por otro lado, hay algunos estudios controlados publicados en los que la EMT se muestra eficaz ayudando a los pacientes a disminuir el consumo de tabaco (Amiaz, Levy, Vainiger, Grunhaus y Zangen, 2009;Eichhammer et al, 2003). Además, se ha demostrado capaz de disminuir el craving en adictos a cocaína y al alcohol (Barr et al, 2008; Camprodon, Martínez-Raga, Alonso-Alonso, Shihy y Pascual- Leone, 2007;De Ridder et al, 2011;Mishra, Nizamie, Das y Praharaj, 2010). Por otro lado, es significativo que se haya publicado también que la EMT puede disminuir el craving a la comida en pacientes con trastornos de la conducta alimentaria (Uher et al, 2005;Van den Eynde et al, 2010).…”
unclassified